2011
DOI: 10.1021/cm2012395
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Fluorination of Soft-Templated Mesoporous Carbons for a High-Power Lithium/Carbon Fluoride Battery

Abstract: Soft-templated mesoporous carbons and activated mesoporous carbons were fluorinated using elemental fluorine between room temperature and 235 °C. The mesoporous carbons were prepared via self-assembly synthesis of phloroglucinol–formaldehyde as a carbon precursor in the presence of triblock ethylene oxide–propylene oxide–ethylene oxide copolymer BASF Pluronic F127 as the template. The F/C ratios ranged from ∼0.15 to 0.75 according to gravimetric, energy dispersive X-ray spectroscopy, and X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 42 publications
3
80
0
Order By: Relevance
“…Nevertheless, in the case of carbonaceous lattices, which are highly reactive because of their size (carbonaceous nanomaterials such as SWCNTs [27], graphene [60], or fullerenes [29] or their high surface area (highly porous materials [20], the reaction with fluorine gas may result in decomposition as volatile species (CF 4 and C 2 F 6 ) in addition to fluorination (grafting of fluorine atoms). Because of the loss of carbon atoms, the fluorine content is underestimated using weight uptake.…”
Section: Nmrmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in the case of carbonaceous lattices, which are highly reactive because of their size (carbonaceous nanomaterials such as SWCNTs [27], graphene [60], or fullerenes [29] or their high surface area (highly porous materials [20], the reaction with fluorine gas may result in decomposition as volatile species (CF 4 and C 2 F 6 ) in addition to fluorination (grafting of fluorine atoms). Because of the loss of carbon atoms, the fluorine content is underestimated using weight uptake.…”
Section: Nmrmentioning
confidence: 99%
“…Recently, Fluvio et al [20] reported the modification of ordered carbonaceous materials by fluorine gas, which exhibited higher energy and power densities and faster reaction kinetics at high current density in primary lithium batteries compared to commercial carbon fluorides. It is worth mentioning that studies concerning the fluorination of porous carbonaceous materials are rather limited, most of the works being devoted to graphite fluorides, which are already recognized as performing materials in industrial applications as electrodes for primary batteries and solid lubricants [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CeF bonds of CF x materials prepared by the roomtemperature catalytic approach have more ionic character than compounds using the high-temperature approach, leading to cells with higher voltage and better kinetics [97,99,103]. The less invasive low-temperature process also helps preserve the pore structures of various carbon materials [107]. However, residual catalysts may be present causing aging issues and need to be removed by thermal treatment [103,108].…”
Section: Cf Xmentioning
confidence: 99%
“…For example, increase in adsorption capacity [177], as well as an increase in conductivity and performance in super-capacitors [178] and batteries [179] have been reported based on targeted modification of surface chemistry. Oxygen [180], fluorine [181][182][183], nitrogen [184,185], and sulphur [186,187] [ 189] and Im et al [190] report fluorination of phenolic activated carbon and polyacrylonitrile-based activated carbon nanofibers to enhance electrochemical capacitance and CH 4 storage respectively. Leroux and Dubois [191] demonstrate improved performance of primary Li + ion batteries using ordered mesoporous carbonaceous materials having various amounts of fluorine, with tuning the fluorination temperature.…”
Section: Functionalization and Surface Modification Of Carbon Materialsmentioning
confidence: 99%